Impactos da pandemia Covid-19 no serviço de delivery do setor de fast food no público universitário - Reis, Denise Eduarda da Silva (Universidade Federal de São Carlos, 2022)
With the first case reported in December 2019 by the World Health Organization, Covid-19 has spread across all continents, causing major impacts. Bringing fears and uncertainties, the population found it impossible to carry out routine activities, consequently starting to use the delivery service more frequently, especially the university public who already consumed this type of service usually. On the other hand, entrepreneurs acted quickly in the face of changing consumer behavior, and started offering delivery service in their establishments. The present work aims to analyze the behavior of demand and its impacts on the delivery system of fast food restaurants during the Covid-19 pandemic, comparing data referring to the years prior to the beginning of the pandemic with the pandemic period, specifically for the public of university students. from the Federal University of São Carlos (UFSCar), Sorocaba Campus. Through a survey, the results obtained with the collected sample pointed out that the pandemic impacted on a 71% increase in demand for fast food delivery service with the arrival of Covid-19 in Brazil.
Impacts of the Covid-19 pandemic on the delivery service of the fast food sector in the university public
Keywords: Delivery; Pandemia; Covid-19; Fast food; Delivery; Pandemic; Covid-19; Fast food; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO